2017
DOI: 10.3390/cosmetics4040051
|View full text |Cite
|
Sign up to set email alerts
|

Whitening Agents from Reseda luteola L. and Their Chemical Characterization Using Combination of CPC, UPLC-HRMS and NMR

Abstract: Skin whitening agents occupy an important part of the dermo-cosmetic market nowadays. They are used to treat various skin pigmentation disorders, or simply to obtain a lighter skin tone. The use of traditional skin bleachers (e.g., hydroquinone, corticoids) is now strictly regulated due to their side effects. When considering this and the growing consumers' interest for more natural ingredients, plant extracts can be seen as safe and natural alternatives. In this perspective, in vitro bioassays were undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…The most detailed studies so far are those by Moiteiro et al, Marques et al,Mantzouris et al and Otłowska et al [24,26,28,34]. In contrast, the study by Burger is confusing with the major peaks reported as unknown [35]. Further, it is unclear where exactly luteolin-4 -O-glucoside elutes.…”
Section: Introductionmentioning
confidence: 99%
“…The most detailed studies so far are those by Moiteiro et al, Marques et al,Mantzouris et al and Otłowska et al [24,26,28,34]. In contrast, the study by Burger is confusing with the major peaks reported as unknown [35]. Further, it is unclear where exactly luteolin-4 -O-glucoside elutes.…”
Section: Introductionmentioning
confidence: 99%
“…Para S. zeamais, también presentaron buenos resultados los extractos en alcohol de N. glauca, P. clandestinum y R. luteola, al ocasionar más del 42 % de mortalidad en este insecto. Este efecto de la Gualda (R. luteola) está relacionado con sus metabolitos secundarios que contienen azufre y nitrógeno (Burger et al 2017). En P. truncatus, dos de los extractos en alcohol, presentaron resultados sobresalientes al ocasionar una mortalidad de 62.5 % (R. luteola) y 50 % (S. ballotiflora); así como los extractos alcohólicos de N. glauca y P. clandestinum, que causaron más del 40 % de mortalidad (Tabla 2).…”
Section: Evaluación De Toxicidad De Los Extractos En Laboratoriounclassified
“…For S. zeamais, alcohol extracts of N. glauca, P. clandestinum, and R. luteola also presented worthy performance, causing more than 42 % mortality in this insect. This effect of Gualda (R. luteola) is related to its secondary metabolites containing sulfur and nitrogen (Burger et al 2017). In P. truncatus, two of the extracts in alcohol presented outstanding results by causing mortality of 62.5 % (R. luteola) and 50 % (S. ballotiflora); as well as the alcoholic extracts of N. glauca and P. clandestinum, which caused more than 40 % mortality (Table 2).…”
Section: Toxicity Evaluation Of the Extracts In The Laboratorymentioning
confidence: 99%